Richness of Dendrocephalus (Branchiopoda, Anostraca) in Brazil with the description of two new species - Rabet, Nicolas; Lacau, Sébastien; Bozelli, Reinaldo L. (European Journal of Taxonomy, 2018)
We present an overview of the morphological diversity and geographical distribution of the anostracan genus Dendrocephalus Daday, 1908, and describe two new species: D. aranai sp. nov. from Jequitinhonha in the state of Minas Gerais and D. xikrini sp. nov. from the Carajás Mountains (Serra dos Carajás) in the state of Pará. These species have important similarities to D. goiasensis Rabet & Thiéry, 1996 and D. thieryi Rabet, 2006, respectively, but differ from them and each other through a combination of characters that are essentially unique to the endopods, and frontal appendage branch 2A and branch 2D. We also partly redescribe D. carajaensis Rogers, Gomes & Vieira, 2012, which shows a particular intra-populational variability in branch 2A and 2D III of the frontal appendage, a type of polymorphism that was also recently observed in D. orientalis Rabet & Thiéry, 1996 and which must now be taken into account in taxonomy. In terms of the distribution of species of Dendrocephalus in Brazil, we suggest that several other species are probably present in the Amazonian, Cerrado and Pantanal Biomes, which remain largely unexplored. A new taxonomic key for the identification of males of the Brazilian species is provided.